P11.16 Denominators matter: trends in neisseria gonorrhoeae incidence among gay, bisexual and other men who have sex with men (gbmsm) in the us – findings from the std surveillance network (ssun) 2010–2013. (13th September 2015) - Stenger, MR; Bauer, H; Torrone, E
Abstract : Introduction: Inequalities in Neisseria gonorrhoeae burden by sexual minority status have been observed in the United States but are difficult to characterise. GBMSM status of gonorrhoea cases is not routinely collected for reported cases and GBMSM population estimates at the level of geography necessary to most usefully inform public health responses are not readily available. Incidence trends and inequalities among GBMSM have not been described across multiple jurisdictions. Methods: A random sample of reported gonorrhoea cases was interviewed and weighted to estimate GBMSM status of all cases reported in 12 geographically disparate states and/or cities collaborating in SSuN. Census and Gallup opinion polling data were used to estimate size of GBMSM, heterosexual male and female populations by age group at the state, county and city level for 2010–2013. Incidence rates and rate-ratios were calculated comparing incidence trends among GBMSM, heterosexual males and females. Results: The estimated size of GBMSM population varied across SSuN jurisdictions from 2.8% of males in Alabama to 15.4% in San Francisco. The proportion of male gonorrhoea cases attributable to GBMSM also varied by jurisdiction (range: 13.6% to 92.4%). GBMSM incidence increased in SSuN sites from 1, 169.7 cases per 100, 000 in 2010 to 1, 474.4 in 2013, increased modestly among heterosexual men and remained stable among females at 106 cases per 100, 000. The rate-ratio of GBMSM to females and to heterosexual men during the study period ranged from 10.7 to 13.9. The highest incidence among GBMSM across all sites was observed for those aged 25–29 years with estimated annual incidence exceeding 3, 400 cases per 100, 000 across the study period. Conclusion: Gonorrhoea incidence among GBMSM is increasing in a sentinel network of US jurisdictions. Estimates of the size of this population and ascertainment of GBMSM status for reported cases are essential first steps for better understanding the changing epidemiology of gonorrhoea. Disclosure of interest statement: The STD Surveillance Network (SSuN) is funded by the US Centres for Disease Control and Prevention (CDC). No pharmaceutical grants were received in the development of this study.